Arm Strength and Shoulder Flexibility in a Physical Training Curriculum: Predictors of Spin Serve Ball Rotation - Aprilo, Ians; Arfanda, Poppy Elisano; Mappaompo, M. Adam; Hasanuddin, M. Imran; Nurulita, Retno Farhana; Zakaria, Ahmad (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
High ball rotation speed is essential for junior tennis spin serve performance, yet physical training curricula generally neglect it. Designing effective training programs requires identifying physical characteristics that predict high ball rotation. This study examines how arm muscle strength and shoulder flexibility affect spin serve ball rotation speed in junior tennis players. The correlational study included 20 Makassar-based 15–16-year-old male junior athletes who had mastered spin serving. A handgrip dynamometer and 2 kg medicine ball throw test tested arm strength. The back scratch test assessed shoulder flexibility. Kinovea analyzed the ball's rotation speed recorded by a Canon EOS 1100D camera (120 fps). The results showed a strong and significant correlation between arm muscle strength and ball rotation speed (r = 0.68; p < 0.001), as well as a moderately significant correlation with shoulder flexibility (r = 0.51; p = 0.002). A multiple regression analysis indicated that these two factors together made up 58% of the ball rotation performance (R^2 = 0.58), with arm muscle strength making up 42% and shoulder flexibility making up 16%. These findings highlight that optimal spin serve performance is strongly influenced by upper body strength and shoulder mobility, which synergistically enhance racket acceleration and ball brushing mechanics. The implication for junior tennis physical training curricula is the need for structured and measurable emphasis on developing specific arm strength and maintaining optimal shoulder range of motion as key predictors of spin serve effectiveness.